Perkembangan Islam di Malaysia (Suatu Tinjauan Sosio Historis) - Abdullah Renre (Jurnal Adabiyah: Humanities and Islamic Studies, 2012)
In general, Islam and Malay community has been long integrated that has brought about the Islamic values in all aspects of life. This is due to the Malay background has been dominated by Islamic kingdom (sultanate) and Islam organizations had established the Islamic identity and opinion that obliged them to create/build moslem society pioneered by intellectuals, preacers, beurocrats, politicians. Besides, the young Moslem generations who have been highly educated both in and outside Malaysia actively take part in developing the country based on Islamic values. Commonly, Malay community feels that what they are doing now is in the right paths.